1990
DOI: 10.1111/j.1528-1157.1990.tb05354.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Glutathione Peroxidase, Glutathione Reductase, Superoxide Dismutase, Catalase, and Glucose‐6‐Phosphate Dehydrogenase Activities in FeCl3‐Induced Epileptogenic Foci in the Rat Brain

Abstract: This study investigated the relationship between lipid peroxidation, subsequent activation of antioxidative enzymes, and development of iron-induced epilepsy in the rat. Epileptic foci were produced in rat cerebral cortex by intracortical injection of ferric chloride (FeCl3). The epileptic foci were identified by electrocorticography (ECoG). Epileptiform ECoG activity was shown to occur in the contralateral homotopic cerebral cortex as well. We measured levels of lipid peroxides and changes in the activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(73 citation statements)
references
References 53 publications
1
70
1
1
Order By: Relevance
“…60 • 61 Alterations in antioxidant enzyme activities follow chemical-induced seizures. 62 We have found that a brief (1 sec) electroconvulsive shock is sufficient to cause elevated rates of ROS formation in rat cerebral cortex (unpublished data).…”
Section: Seizure Activitymentioning
confidence: 87%
“…60 • 61 Alterations in antioxidant enzyme activities follow chemical-induced seizures. 62 We have found that a brief (1 sec) electroconvulsive shock is sufficient to cause elevated rates of ROS formation in rat cerebral cortex (unpublished data).…”
Section: Seizure Activitymentioning
confidence: 87%
“…It has also been reported that oxidative stress may in part contribute to the pathogenesis of PH in a MCT model [33,34] . The antioxidative defense is largely provided by several enzymes such as SOD, GSH-Px, and CAT [35][36][37] . Meng and coworkers [25] indicated that low doses of SO 2 (22 and 56 mg/m 3 ) caused significant increases in SOD, GSH-Px, and CAT activities in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in glutathione synthesis can result in neurological disorders (Bains and Shaw, 1997;Schweizer et al, 2004), and recent studies have suggested that membrane lipid peroxidation may be involved in epileptogenesis in some experimental models of epilepsy (Kim et al, 1997(Kim et al, , 2000c(Kim et al, , 2002aSingh and Pathak, 1990;Willmore et al, 1986). The production of epileptiform discharges in some forms of experimental epilepsy/convulsion is believed to be mediated by membrane lipid peroxidation initiated by the action of oxygen radicals, which can alter electrophysiologic properties of membranes, such as iongating (Pellmar, 1986).…”
mentioning
confidence: 99%